PENGARUH KUALITAS LAYANAN TERHADAP CITRA PERUSAHAAN, KEPUASAN DAN LOYALITAS PELANGGAN (Studi pada Nasabah Pengguna Produk Tabungan BCA di wilayah Rungkut Mapan, Surabaya) - Anzie, Luthfy Purnanta; Arifin, Zainul (Profit: Jurnal Adminsitrasi Bisnis, 2015)
The purpose of this research was to investigate and explain the significant effect of service quality on corporate image, service quality on customer satisfaction, service quality on customer loyalty, corporate image on customer loyalty, corporate image on customer satisfaction and to customer satisfaction on customer loyalty. This research is an explanatory research that explains the causal relationships between variables by using a quantitative approach. Generalized Structured Component Analysis (GSCA) is used as a method of data analysis, accompanied by hypothesis testing to determine significant effect on the variables that have been determined. Population taken as many as 55 customers who live in the area BCA Rungkut Mapan, Surabaya. The technique used is to provide keuisioner to respondents. The results of this study are of six hypotheses, there is a hypothesis that is rejected is no significant effect of service quality on customer loyalty. Limitation in this research is the narrowness of the region and at least a population sample. So for the next study is expected to extend coverage and increase the study sample, which made a research will be better.Â Â